Instructional Leadership Challenges and Practices of Novice Principals in Rural Schools - Duglas Wieczorek; Carolyn Manard (Journal of Research in Rural Education, 2018)
We report on a phenomenological study of the leadership experiences of six novice, rural public school principals in a midwestern U.S. state. We situated our analysis within existing research on leadership for learning, particularly how novice principals interpreted instructional leadership challenges in the context of rural school leadership. Our fi ndings indicated that principals worked to balance their professional and private lives and were challenged to meet their community's expectations to be visible and engaged. To meet districts' constrained budgetary circumstances, the principals also maintained overlapping district- and building-level responsibilities. The principals focused heavily on developing relationships and trust among their teachers, students, and parents. The implications of this study demonstrate a need to develop new leaders' understanding of rural school community expectations; develop skills to fulfi ll expanding job responsibilities; and supplement leadership preparation, mentoring, and professional development programs regarding the specialized needs of rural school leaders.